Mediated Associations Between Religious Coping, Self-Regulation, and Psychological Distress Vary for Young Muslim Men and Women in Lahore, Pakistan - Fatima, Shameem (Journal of religion and health, 2022)
The main aim of the study was to assess the direct, mediated, and conditional mediated associations among religious coping, self-regulation, and psychological distress in young Muslim adults while analyzing gender as a moderator of these mediated associations. Based on a sample of 247 young adults from Lahore, Pakistan (M age = 21.31, SD = 2.40; 51% women, 49% men), it was found that self-regulation mediated the negative associations of positive religious coping with stress and anxiety and the positive association of negative religious coping with stress. Further, it was found that mediated associations were stronger and significant in young men compared to women. The implications of the findings concerning gender differences in association between religious coping, self-regulation, and psychological distress are discussed.